Developing a risk‐based trading scheme for cattle in England: farmer perspectives on managing trading risk for bovine tuberculosis. (11th February 2017) - Little, R.; Wheeler, K.; Edge, S.
Abstract : This paper examines farmer attitudes towards the development of a voluntary risk‐based trading scheme for cattle in England as a risk mitigation measure for bovine tuberculosis (bTB). The research reported here was commissioned to gather evidence on the type of scheme that would have a good chance of success in improving the information farmers receive about the bTB risk of cattle they buy. Telephone interviews were conducted with a stratified random sample of 203 cattle farmers in England, splitting the interviews equally between respondents in the high‐risk area and low‐risk area for bTB. Supplementary interviews and focus groups with farmers were also carried out across the risk areas. Results suggest a greater enthusiasm for a risk‐based trading scheme in low‐risk areas compared with high‐risk areas and among members of breed societies and cattle health schemes. Third‐party certification of herds by private vets or the Animal and Plant Health Agency were regarded as the most credible source, with farmer self‐certification being favoured by sellers, but being regarded as least credible by buyers. Understanding farmers' attitudes towards voluntary risk‐based trading is important to gauge likely uptake, understand preferences for information provision and to assist in monitoring, evaluating and refining the scheme once established.